Is the Tunisian Central Bank following a Linear or a Nonlinear Augmented Taylor Rule? - Lamia, Beldi; Djelassi, Mouldi (International Journal of Economics and Financial Issues, 2020)
The political transition in the Arab Spring countries has been accompanied by a deterioration of economic and financial indicators like in the Tunisian case. This paper aims to get a deeper understanding of the nature of the rule that reflects the behavior of the Tunisian monetary authority in the current dominance of economic and financial instability. In particular, this paper assesses whether the Tunisian Central Bank is indeed following a linear or a non linear augmented Taylor rule. For our purpose, we use a forward looking version of Taylor rule augmented by including the effect of exchange rate to estimate the linear and the nonlinear models. A smooth transition regression model is used to estimate the nonlinear rule. The results obtained imply that the Tunisian Central Bank follows a nonlinear Taylor rule in the conduct of monetary policy. In addition, our evidence suggests that the reaction of monetary authority in Tunisia to the deviation of forecasts of inflation rate, output gap and exchange rate changes in terms of magnitude and statistical significance across the high and low interest rate regimes. In particular, when the lagged interest rate is above the threshold level of 4.76%, the main objective of the policy makers is to fight the inflation rate and to limit the depreciation of exchange rate rather than to boost the economic activity. Keywords: Taylor rule, smooth transition regression model, interest rate reaction function, nonlinearity JEL Classifications: C22, E17, E43, E52, E58 DOI: https://doi.org/10.32479/ijefi.8975